Profiling the approach to the investigation of viral infections in cases of Sudden Unexpected Death in Infancy (SUDI) in the Western Cape Province - Burger, Marilize Cornelle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.